Intersex conditions / disorders of sex development - Rey, Rodolfo (Henry Stewart Talks, 2023)
Concepts of sex and gender, Biologic aspects of sex, Chromosomal sex, Genetic sex, Gonadal sex, Etio-pathogenic classification, Dysgenesis, AMH (Anti Mullerian Hormone), DSD (Disorders of Sex Development) management, Congenital adrenal hyperplasia (CAH)